2018
DOI: 10.1002/jso.25119
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with larger soft‐tissue sarcomas, more surgical complications, and more complex wound closures (obesity leads to larger soft‐tissue sarcomas)

Abstract: These findings suggest that obesity is associated with larger tumors, a higher incidence of wound complications, and greater use of complex wound-closure methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The rate of all complications including CD-grade 1 in our cohort of soft tissue sarcomas of the chest wall with 44% was comparable to a study of Slump et al on STS of various locations that required flap coverage and Montgomery et al on extremity STS [25,26].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The rate of all complications including CD-grade 1 in our cohort of soft tissue sarcomas of the chest wall with 44% was comparable to a study of Slump et al on STS of various locations that required flap coverage and Montgomery et al on extremity STS [25,26].…”
Section: Discussionsupporting
confidence: 86%
“…In univariate analysis, obesity was associated with higher wound complications in our cohort. Accordingly, Montgomery et al found obesity to be associated with both a larger tumor size and higher morbidity as causes of wound complications, and thus that it is eliminated by other factors in multivariate analysis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the levels of these complication rates are in accordance with the literature, all efforts should be made to further decrease those levels. However, the risk of such major complications may not only be related RT, but possibly even more to the patient [20] and individual tumor characteristics [21] and tumor specific molecular mechanisms [22, 23]. In addition, different surgical resection modes (wide excision or compartment resection in contrast to simple resection [24]), differences in preoperative treatments, and various localizations (maybe affecting of neurovascular structures bones or joints) of soft tissue sarcomas may play a role in major complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 In adults, the association between obesity and multiple complications such as impaired or totally EDITORIAL failed cutaneous wound healing, particularly following surgery, has been identified by various groups. [51][52][53][54][55][56][57][58][59][60] Being overweight or obese significantly increases the likelihood of infection-related complications compared with those within a healthy weight range. 61 There are many factors that contribute to the chronicity of infection in obese people.…”
Section: Overweight and Obesitymentioning
confidence: 99%